PEMANFAATAN PERILAKU HIDUP BERSIH PADA ANAK USIA DINI UNTUK MENCEGAH RESIKO STUNTING DI KELURAHAN BAJAWA - Viktoria Dhihu; Elisabeth Tantiana Ngura; Yasinta Maria Fono; Efrida Ita (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the use of Clean and Healthy Living Behavior (PHBS) in early childhood as an effort to prevent the risk of stunting in Bajawa Village. Stunting is a chronic nutritional problem that is not only influenced by lack of nutritional intake, but also by environmental sanitation factors, recurrent infections, and family parenting. This study uses a qualitative approach with observation, interview, and documentation methods. The research informants consisted of parents of early childhood, Posyandu cadres, and health workers. The data were analyzed descriptively to describe the conditions of PHBS implementation, children's food consumption patterns, environmental sanitation, and the role of parents in supporting children's growth and development. The results of the study showed that most of the children had applied several PHBS indicators such as washing their hands with soap, maintaining personal hygiene, and participating in growth monitoring at the Posyandu. Children's food consumption patterns are already regular in the frequency of meals, but variation and nutritional balance still need to be improved, especially in the consumption of vegetables, fruits, and various protein sources. The general environmental sanitation condition is quite good, characterized by the availability of clean water and latrines, although waste management and drainage still need improvement. The active role of parents has proven to be an important factor in forming healthy living habits in children.